Evaluation of the Clinical Characteristics and Associated Factors of Adult Early-Onset Type 2 Diabetes Mellitus Patients in Tertiary Care Hospitals (KYAMC Journal, 2026)
Background: Adult early-onset type 2 diabetes mellitus (T2DM), is increasing worldwide, including Bangladesh. The clinical characteristics and patterns of complications differ significantly between adult early-onset (